A female neonate with absent anal opening and dug perineum: Think high - Parveen Kumar; Nitin Jain; Vivek Viswanathan; Rishabh Jain (EL-Med-Pub, 2020)
Background: A female neonate with anorectal malformation (ARM) may have one, two, or three openings in the perineum. One opening represents cloaca while three openings usually suggest low ARM. Females with two openings in the perineum may be ARM without any fistula, rectovaginal fistula, or absent vagina. The association of ARM with multiple intestinal atresias and malrotation is rare. Case Presentation: We present here a case of a female neonate with two perineal openings, whose perineum was explored by a general surgeon without any radiological investigation and was later found to have a high ARM, multiple jejunal and ileal atresia with malrotation. Conclusion: ARM associated with small bowel atresia and malrotation are rarely described. Such cases require management in Pediatric surgery settings.